Fundamentals of protein chromatography: protein chromatography - Burgess, Richard R. (Henry Stewart Talks, 2020)
History of chromatography, Forces and properties of proteins as handles for fractionation, Types of chromatography, Chromatography components, HPLC, Trouble shooting some chromatography problems, Protein purification for pharmaceutical applications